Influence of orofacial myofunctional therapy in the efficacy and efficiency of open bite treatment with fixed palatal crib: a randomized clinical trial - Marques, Thagid Yasmin Leal Almeida (2024)
Introduction: This study aimed to compare the efficacy and efficiency of anterior open bite (AOB) treatment in the mixed dentition with fixed palatal crib alone versus associated with brief orofacial myofunctional therapy (OMT); compare the changes in tongue pressure resulting from these protocols; and to determine whether the changes in tongue pressure during treatment are predictor factors for the open bite correction. Methods: PC group consisted of patients treated with a fixed palatal crib alone. PCOMT was composed of patients treated with a fixed palatal crib associated with a weekly session of OMT for the first 2 months of therapy. Lateral headfilms and tongue pressure examination using the Iowa Oral Performance Instrument (IOPI) were performed at pre-treatment (T1) and after the open bite correction or after 12 months of treatment (T2). Intergroup comparisons were performed using analysis of covariance using an initial anterior open bite as a co-variate (p<5%). Linear regression analysis was performed to evaluate the association between tongue pressure and the overbite correction. Results: PC group comprised 16 patients (3 male, 13 female) with a mean age of 8.65 years (SD=0.93). PC-OMT group was composed of 16 patients (9 male, 7 female) with a mean age of 7.97 years (SD=1.00). After the follow-up period, all patients showed an overbite improvement. No intergroup differences for overbite changes were found. After the observation period, a clinical positive overbite was achieved 86.6% of PC group and 61.5% of PC-OMT group. Tongue pressure increased in all variables analyzed in both groups, but with significantly difference between groups only during swallowing, presenting lower values in the group treated with OMT. Changes in tongue pressure was not associate to overbite correction. Conclusions: Similar efficacy and efficiency for anterior open bite treatment in the mixed dentition with fixed palatal crib alone or associated with brief OMT was observed. Orofacial myofunctional therapy associated with palatal crib controlled the increase in swallowing pressure. Changes in tongue pressure was not a predictive factor for open bite correction in the mixed dentition.